2005
DOI: 10.1111/j.1471-0528.2005.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired haemophilia and postpartum haemorrhage treated with internal pudendal embolisation

Abstract: Case report A 32 year old healthy nulliparous woman had a normal delivery at term. Primary postpartum haemorrhage of 500 mL occurred within minutes of delivery and settled with an infusion of syntocinon and suturing of a vaginal tear. Bleeding recurred within hours and she underwent examination in theatre with evacuation of clots and placental tissue and resuturing. The estimated blood loss was 2600 mL and she had a three-unit blood transfusion. On the following two days, she was transfused a further six units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The reports dated from 1976 [25] to 2010 [26], and the age of patients ranged from 16 to 39 years [27,28]. The majority of the cases reported management of postpartum hemorrhage with tranexamic acid [29,30,27,[31][32][33][34][35][36][37]26]. Seven studies reported antepartum hemorrhage [25,[38][39][40][41][42][43].…”
Section: Case Reportsmentioning
confidence: 98%
See 3 more Smart Citations
“…The reports dated from 1976 [25] to 2010 [26], and the age of patients ranged from 16 to 39 years [27,28]. The majority of the cases reported management of postpartum hemorrhage with tranexamic acid [29,30,27,[31][32][33][34][35][36][37]26]. Seven studies reported antepartum hemorrhage [25,[38][39][40][41][42][43].…”
Section: Case Reportsmentioning
confidence: 98%
“…Seven studies reported antepartum hemorrhage [25,[38][39][40][41][42][43]. Hemorrhage associated with hematological disorders was reported in nine cases [44,29,30,31,28,[33][34][35][36][37]. The most common hematological disorder mentioned was Bernard Soulier syndrome [29,[34][35][36], followed by hemophilia [30,33], leukemia [28], other platelet disorders such as Glanzmann's thrombasthenia [44], Evan's syndrome [31], and platelet storage pool disease [37].…”
Section: Case Reportsmentioning
confidence: 98%
See 2 more Smart Citations
“…Selective angiographic embolisation requires only local anaesthesia. It may be carried out even on patients with a severe coagulopathy [22], although clotting abnormalities are preferably corrected before the procedure. If the blood loss originates from the uterus, both uterine arteries should be occluded because of the existence of innumerable vascular anastomoses between the left and the right side of the uterus.…”
Section: Treatment Of Hypotonic Haemorrhagementioning
confidence: 99%